Myxoid angiomatoid fibrous histiocytoma. report of an uncommon neoplasm with a literature review - Marwa Mohamed Abd El Aziz; Rania Gaber Aly; Samir S Amr (Advances in Medical, Pharmaceutical and Dental Research, 2022)
Angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue tumor usually seen in the extremities of children and adolescents. Classically AFH presents as a painless cystic mass that shows blood filled spaces on cut section and bland histiocyte-like cells on microscopic examination. Predominance of myxoid stroma is a rare finding in AFH, usually seen with other classical features. We herein report a case of myxoid AFH with both unusual clinical presentation and uncommon histopathological features with a review of literature.